Event-related potentials reflect individual differences in age-invariant auditory skills. - McArthur, G; Bishop, D (2002)
Previous work has found that auditory event-related potentials show maturational changes, with latency and amplitude of late components (N1 and P2) decreasing and increasing with age respectively. Our goal was to test the hypothesis that these changes reflect increased speed of neural processing in the auditory system. Thirty-three listeners, aged 10-50 years, were tested on a frequency discrimination task and an auditory backward recognition masking task. P1 and N1b event-related potential components were measured to tones. The N1b became larger and earlier with age, and the latency of P1 decreased with age. However, thresholds on the behavioural tasks did not change with age. Nevertheless, individual differences in the peak amplitude of N1b were independently related to frequency discrimination and degree of masking. Thus, the relationship that does exist between individual differences in psychoacoustic performance and the auditory N1b reflect a stable characteristic of the individual rather than a maturational change.